Pax8 as a useful adjunct marker to differentiate pancreatic serous cystadenoma from clear cell renal cell carcinoma in both cytologic and surgical specimens - Zhikai Chi; Jing Xu; Dipti M. Karamchandani; Lan Peng (BMC, 2023)
Abstract Background Histomorphological differentiation between pancreatic serous cystadenoma (SCA) and clear cell renal cell carcinoma (RCC) can be challenging. We aimed to study Paired box 8 protein (Pax8) expression profile in cytologic and surgical specimens with pancreatic SCA to assess its utility as a differentiating marker from clear cell RCC. Methods We characterized Pax8 immunohistochemistry in 33 patients with pancreatic SCA (23 surgical resections and 10 cytology specimens). Nine cytology specimens from metastatic clear cell RCC involving pancreas were used as control tissue. Electronic medical records were reviewed to retrieve clinical information. Results All 10 pancreatic SCA cytology specimens, and 16 of 23 pancreatic SCA surgical resections showed absent Pax8 immunostaining, while the remaining 7 surgical resection specimens showed 1%-2% immunoreactivities. Islet and lymphoid cells adjacent to the pancreatic SCA expressed Pax8. In contrast, the proportion of Pax8 immunoreactivity ranged from 50 to 90% (average of 76%) in nine cases of metastatic clear cell RCC involving pancreas. Using a 5% immunoreactivity cutoff, all cases of pancreatic SCA are interpreted as negative for Pax8 immunostains while all cases of metastatic clear cell RCC involving pancreas are interpreted as positive for Pax8 immunostains. Conclusions These results suggest that Pax8 immunohistochemistry staining can be a useful adjunct marker to differentiate pancreatic SCA from clear cell RCC in clinical practice. To the best of our knowledge, this is the first large-scale study of Pax8 immunostaining on surgical and cytology specimens with pancreatic SCA.